PENGUATAN IDENTITAS NASIONAL INDONESIA MELALUI PERENCANAAN PEMBANGUNAN BERBASIS LEMBAGA KEMASYARAKATAN - ACHYAR HANIF SIREGAR (Develop: Jurnal Ekonomi Pembangunan, 2021)
Indonesia is a country that has a national identity that is realized because of the thousands of islands inhabited by various ethnic groups with various spoken languages, six officially embraced religions, and other diversity that have their own uniqueness.Indonesia's national identity should be a potential that can be utilized to solve nation's current problems, such as the number of unemployed people in Indonesia which reached 9.77 million people in August 2020.However, Indonesia's national identity is still vulnerable to horizontal social conflict of ethnicity, religion, race, and groups. This research purpose is to identify Indonesia's national identity and analyze its strengthening through development planning based on Social Institution. The research method used is literature study. The result shows that efforting of strengthening Indonesia's national identity through development planning based on Social Institution can be carried out through increasing the leadership capacity of the Rukun Tetangga and Rukun Warga, reforming the nature of Customary Institutions, focusing on Community Empowerment Institutions with local wisdom, and eventing the Karang Taruna documentation award. Social Institution can be an ideal container because it has the advantage as the closest institution to communities throughout Indonesia. Social Institutions that produce participatory, tolerant, empowered, and innovative societies which are considered to become one maximum unit in strengthening Indonesia's national identity.